Letter from Jane Tolmach and Adele Leopold - Jane Tolmach::::::; Adele Leopold:::::: (1970)
In this November 11, 1970 letter, Jane Tolmach and Adele Leopold congratulate Democratic nominees on their campaigns and note that although Reagan won the governorship, Democrats secured a legislative majority. They remind nominees about the upcoming Key Women Award Party and request the names and addresses of women volunteers who should be honored for their campaign work.